Equipmentality as a Pharmakon - Khalil, Sherif (AUC Knowledge Fountain, 2024)
One must lose the world to know himself, if in his attempt to know the world he lost himself. In this thesis, I argue that equipment is a pharmakon in that its harm lies in the service it is supposed to provide. Through equipment one gets to have a practical sense of the world. But, the world in this sense is a world for everyone and for no one in particular, that is, it is made to the measure of the average person who has no aspirations to realize his authenticity. That is how equipment helps us practically make sense of the world, and, simultaneously, entraps us in that world without allowing us to know who we really are and what we could be. However, I argue that a possible way out of that slumber is to bring in one’s authentic presentiments when dealing with equipment at the cost of “violating” it. For if equipment ordinarily dictates to be used in light of its rhythm, a violation will take place if one was to go after his own potentialities. Hence, equipment is a pharmakon whose poison is embodied in its service and its remedial aspect lies in its violation.